Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di SDN 02 Talago Sariak Kota Pariaman - Novri Yaldi; Silvia Roza (STKIP Andi Matappa Pangkep, 2024)
This research aims to find out and describe the role of the Principal in Improving the Quality of Education at SDN 02 Talago Sariak. This research is qualitative research with a descriptive approach. This is because the researcher will present an overview of the role of the school principal using data obtained through observation, interviews and documentation. The results of this research show that the role of the school principal, which includes educator, manager, administrator, supervisor, leader, innovator and motivator, has been carried out very well. With a good character, firm but motherly, disciplined and open in financial matters, always discussing when there is a problem or something that needs to be decided. Even though in terms of infrastructure it is still not stable, during the principal's leadership this school has experienced many improvements compared to the previous one.